2016
DOI: 10.1111/geb.12431
|View full text |Cite
|
Sign up to set email alerts
|

Linking basin‐scale connectivity, oceanography and population dynamics for the conservation and management of marine ecosystems

Abstract: Aim Assessing the spatial structure and dynamics of marine populations is still a major challenge in ecology. The need to manage marine resources from ecosystem and large‐scale perspectives is recognized, but our partial understanding of oceanic connectivity limits the implementation of globally pertinent conservation planning. Based on a biophysical model for the entire Mediterranean Sea, this study takes an ecosystem approach to connectivity and provides a systematic characterization of broad‐scale larval di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 81 publications
4
100
0
Order By: Relevance
“…), and although basin‐scale models are known to poorly simulate complex coastal currents, our statistical analyses derived from such model provide signals consistent with both inter‐annual variability and geographical discrepancies of LR associated with local topography and hydrodynamics (Dubois et al. ). Moreover, we demonstrate that our connectivity metrics integrate both larval retention and exchanges (Watson et al.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…), and although basin‐scale models are known to poorly simulate complex coastal currents, our statistical analyses derived from such model provide signals consistent with both inter‐annual variability and geographical discrepancies of LR associated with local topography and hydrodynamics (Dubois et al. ). Moreover, we demonstrate that our connectivity metrics integrate both larval retention and exchanges (Watson et al.…”
Section: Discussionsupporting
confidence: 76%
“…Following Dubois et al. (), who showed that the greater deviation between SR and LR, the more pronounced is the source or sink behavior, it indicates that the 6 subpopulations mostly behave as sources in which larval export dominates import (Fig. b).…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations